2016
DOI: 10.3389/fmicb.2016.00654
|View full text |Cite
|
Sign up to set email alerts
|

Networks of Host Factors that Interact with NS1 Protein of Influenza A Virus

Abstract: Pigs are an important host of influenza A viruses due to their ability to generate reassortant viruses with pandemic potential. NS1 protein of influenza A viruses is a key virulence factor and a major antagonist of innate immune responses. It is also involved in enhancing viral mRNA translation and regulation of virus replication. Being a protein with pleiotropic functions, NS1 has a variety of cellular interaction partners. Hence, studies on swine influenza viruses (SIV) and identification of swine influenza … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 128 publications
1
17
0
Order By: Relevance
“…High salt and RNAse treatments of these fraction, as well as R38A and K41A mutations in NS1, did not increase NS1 solubility. This indicates that additional transcriptional regulation mechanisms involving NS1 interactions with cellular factors may take place, which is in agreement with previous findings showing that NS1 non-conserved residues outside dsDNA/RNA binding site may interact with chromatin-associated factors [49,50].…”
Section: Discussionsupporting
confidence: 93%
“…High salt and RNAse treatments of these fraction, as well as R38A and K41A mutations in NS1, did not increase NS1 solubility. This indicates that additional transcriptional regulation mechanisms involving NS1 interactions with cellular factors may take place, which is in agreement with previous findings showing that NS1 non-conserved residues outside dsDNA/RNA binding site may interact with chromatin-associated factors [49,50].…”
Section: Discussionsupporting
confidence: 93%
“…Several molecular determinants have already been identified that govern the pathogenicity of avian influenza virus for mammals, such as amino acid substitutions in the ribonucleoprotein (RNP) complex (Gabriel et al, 2005;Salomon et al, 2006;Song et al, 2009;Sun et al, 2015), the mutations involved in the ability of NS1 proteins to restrict the induction of the host interferon response (Li et al, 2006;Thulasi Raman and Zhou, 2016), the length of the NA stalk (Zhou et al, 2009). However, most of these studies focused on H5 subtype of influenza viruses, and the pathogenic mechanism of H9N2 viruses for mammals is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…To ask whether F3 proteins could be presented by MHC I and recognised by the immune system, as well as to test whether in principle F3 ORFs could be translated, we created a modified IAV containing a frame 3 insertion of OVAI (OVA 257-264; SL8; SIINFEKL), a class I-restricted epitope of ovalbumin. We inserted OVAI into segment 8 (NS) of the virus, deleting a number of naturally-occurring F3 stops to create a cryptic 5′ ORF so that we could exploit the tolerance of a linker region in the NS1 gene to insertion mutations (NS-F3.SIIN; Supplementary Fig S9) [36]. To ask whether the F3 5′ ORF was translated we treated bone marrow derived dendritic cells (BMDCs) with a sonicated IAV antigen preparation and then incubated these with purified CD8 T cells from OTI mice (Fig 3F).…”
Section: Resultsmentioning
confidence: 99%